Perbandingan Tingkat Kelelahan Kerja Perawat Antara yang Melayani Pasien COVID-19 dan Non COVID-19 di RSUP Dr Kariadi Semarang - Nanang Qosim; Joko Wiyanto; Arip Susianto; Sri Listyaning Wulan; Hikmi Muharromah Pratiwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Health services during the COVID-19 pandemic trigger a high risk of fatigue among nurses in all inpatient rooms, especially the isolation rooms for patients with COVID-19. Fatigue can reduce the performance of nurses and health services. Objective: This study compares nurses' work fatigue levels between those who serve in the COVID-19 room and those who serve non-COVID-19 at RSUP Dr. Kariadi Semarang. Methods: A comparative study with consecutive sampling involving 96 nurses (46 COVID-19 ward nurses and 50 non-COVID-19 ward nurses). The survey was conducted by filling out a Subjective self-rating test questionnaire from the Industrial Fatigue Research Committee (IFRC) via a Google form. Analysis of fatigue differences was performed using the Chi-Square test. Result: The mean IFRC score of respondents was 47.19 ± 12.97, while most nurses experienced low levels of fatigue (67.71%, n=65). There was no significant difference in the level of nurse fatigue in the COVID-19 and non-COVID-19 isolation rooms (p = 0.169, x2 = 1.89). Uncomfortable work environment (t = -2.50, p = 0.014), anxiety feeling at work (F = 3.57, p = 0.032), and shift system (t = -2.34, p = 0.018) significantly correlated with the level of nurses' fatigue.Conclusion: The work environment, shift system, and feelings at work can affect nurses' fatigue levels. Therefore, hospital policies and regulations are necessary to reduce work fatigue for health workers